(untitled) (Boletín Semillero de Investigación en Familia, 2024)
This article shows the importance of adopting the comfort model proposed by Katharine Colcaba of adopting the comfort model proposed by Katharine Colcaba as a theoretical basis for theoretical basis in the activities that are performed by the nursing professional to the patients patients who are installed in the Intensive Care Unit (ICU). Intensive Care Unit (ICU). The analysis of comfort in ICU patients requires a comprehensive and multidisciplinary requires a comprehensive and multidisciplinary approach. Environmental factors, pain pain management, mobility, communication, self-care, nutrition, family involvement and technology, family involvement and technology play crucial roles in the patient’s well-being. This leads to the implementation of evidence-based interventions and evidence-based interventions and maintain an ongoing assessment of comfort that can significantly improve patient significantly improve the ICU patient experience and recovery